Indução de resistência no manejo da fusariose do tomateiro em São Luis-MA - Campos Neto, José Ribamar Muniz (2013)
The tomato (Solanum lycopersicon L.) has its origin in the Andean area of South America and belongs to the Solanaceae family. This culture is affected by various fungal diseases among them the Fusarium wilt caused by Fusarium oxysporum f. sp. lycopersici Snyder & Hansen. In Maranhão, the family farmer uses wrongly a lot of chemicals to control plant pathogens in the culture tomato. Been occurring environmental and social impacts throughout the state. A growing interest in alternative viable and efficient control of pathogens and the resistance inducers have shown promising results and efficient. In order to study the induction of resistance to fusarium wilt of tomato control we used commercial products ASM, Agro-Mos, Chitosan, Biopirol and neem oil on mycelial growth and sporulation of F. oxysporum f. sp. lycopersici and induced resistance of tomato to Fusarium, through the expression of enzyme activity related to the inductive process: peroxidase, polyphenol oxidase and β-1,3-glucanase. Was added different concentrations of the products in the culture medium Potato Dextrose Agar (PDA), making up the inoculation of the pathogen and evaluation of mycelial growth and sporulation after 10 days of evaluation. The experiment "in vivo" took place in the greenhouse. the products were powdered on the first pair of leaves, into the point of runoff, in Santa Cruz variety of plants grown 25 days on soil autoclaved. The inoculation of the pathogen occurred after five days at a concentration of 106 conidia / ml. We evaluated the severity of the disease based on rating scale. The enzyme activity was determined using a specific protocol for each enzyme. The results demonstrate that neem oil controlled mycelial growth and sporulation of the pathogen, whereas the ASM had influence only on sporulation. Decrease of severity of tomato Fusarium. Highlight the Neem oil, Agro-Mos and Biopirol by significant expression of Peroxidase, Polyphenoloxidase and β-1,3-glucanase, respectively